Teknologi Hidrotermal Sebagai Solusi Cepat Pengolahan Sampah Organik Menjadi Pupuk - Dewanti, Dian Purwitasari; Wiharja, Wiharja; Hanif, Muhammad; Nugroho, Rudi (Jurnal Teknologi Lingkungan, 2020)
ABSTRACT Hydrothermal technology is a promising new technology that can turn organic waste into value-added, eco-friendly, and sustainable products. In this research, the hydrothermal reactor's performance for treating the food wastes into solid and liquid fertilizer was investigated. Hydrothermal reactor with SS 316 steel material with a maximum capacity of 100 kg per batch is equipped with a cooling water jacket. Raw vegetable wastes and water with a ratio of 1:1 were added into a mixing container. The waste slurry was transferred through the pump into the reactor. The hydrothermal process is carried out at a pressure of 5 bar or a temperature of around 160 °C for 30 and 60 min. The results showed that the hydrothermal process treated the vegetable waste at 120 minutes at a temperature of 160 °C and 5 bar pressure. Solid products showed a higher C/N ratio and N + P2O5 + K2O content in the process of 30 minutes compared to 60 minutes, which were 12.42 and 5.36, respectively. In comparison, liquid products showed higher results in the 30-minute process than 60-minutes process with the amount of N + P2O5 + K2O and C-organic, respectively 2.23 and 0.31. This result indicated that the hydrothermal process is proven to be able to treat the organic waste into a relatively fast and eco-friendly compost. In the future, it is expected that the big-scale of hydrothermal processes can be an alternative technology in processing  wastes in Indonesia. Keywords: hydrothermal, fertilizer, municipal solid waste, vegetables wastes, eco-friendly technology ABSTRACT Teknologi hidrotermal adalah teknologi baru yang menjanjikan yang dapat mengubah sampah organik menjadi produk yang bermanfaat, ramah lingkungan dan berkelanjutan. Dalam riset ini, unjuk kinerja reaktor hidrotermal untuk mengolah sampah sisa sayuran menjadi pupuk padat dan cair diinvestigasi. Reaktor hidrotermal dengan material baja SS 316 berkapasitas 100 kg per batch dilengkapi dengan dinding air pendingin. Bahan baku sisa sayuran dimasukkan dalam tangki pencampur dengan ditambahkan air pada jumlah yang sama. Setelah berbentuk seperti bubur kasar, sampah dipindahkan melalu pompa ke dalam reaktor. Proses hidrotermal dilakukan pada tekanan 5 bar atau suhu sekitar 160 °C dengan waktu 30 dan 60 menit. Hasil pengujian menunjukkan bahwa proses hidrotermal dengan bahan baku sampah sisa sayuran memerlukan total waktu 120 menit pada temperatur 160 °C dan tekanan 5 bar. Produk padat menunjukkan rasio C/N dan kandungan N + P2O5 + K2O yang lebih tinggi pada proses yang berlangsung 30 menit dibandingkan dengan 60 menit yaitu 12,42 dan 5,36 berturut turut. Produk cair menunjukkan hasil yang lebih tinggi pada proses 30 menit dibandingkan 60 menit dengan jumlah N+P2O5+K2O dan C-organik masing-masing sebesar 2,23 dan 0,31. Hal ini mengindikasikan bahwa proses hidrotermal terbukti dapat mengolah sampah organik menjadi kompos dalam waktu yang relatif cepat dan ramah lingkungan. Kedepan, diharapkan proses hidrotermal pada skala komersial dapat menjadi teknologi alternatif dalam mengolah sampah di Indonesia. Kata kunci: hidrotermal, pupuk, sampah, sisa sayuran, teknologi ramah lingkungan